2005
DOI: 10.1038/sj.jcbfm.9600160
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to Brain Antigens after Stroke is Augmented by Lipopolysaccharide

Abstract: After stroke, the blood-brain barrier is transiently disrupted, allowing leukocytes to enter the brain and brain antigens to enter the peripheral circulation. This encounter of normally sequestered brain antigens by the systemic immune system could therefore present an opportunity for an autoimmune response to brain to occur after stroke. In this study, we assessed the immune response to myelin basic protein (MBP) in animals subjected to middle cerebral artery occlusion (MCAO). Some animals received an intrape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
160
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(164 citation statements)
references
References 45 publications
(47 reference statements)
3
160
0
1
Order By: Relevance
“…The effects of infections in cerebral ischemia have often been tested in experimental models by administration of bacterial lipopolysaccharide at the moment of cerebral ischemia. Lipopolysaccharide increased the likelihood of developing a detrimental autoimmune response to brain antigens with higher presence of B7.1 co-stimulatory molecules on APCs and greater Th1 responses to MBP [123][124][125]. Becker et al [124] also showed that patients who developed an infection after stroke were more likely to show a Th1 response to MBP and glial fibrillary acidic protein, and stronger Th1 responses to MBP were associated to poor functional outcome.…”
Section: Stroke and Infectionmentioning
confidence: 99%
“…The effects of infections in cerebral ischemia have often been tested in experimental models by administration of bacterial lipopolysaccharide at the moment of cerebral ischemia. Lipopolysaccharide increased the likelihood of developing a detrimental autoimmune response to brain antigens with higher presence of B7.1 co-stimulatory molecules on APCs and greater Th1 responses to MBP [123][124][125]. Becker et al [124] also showed that patients who developed an infection after stroke were more likely to show a Th1 response to MBP and glial fibrillary acidic protein, and stronger Th1 responses to MBP were associated to poor functional outcome.…”
Section: Stroke and Infectionmentioning
confidence: 99%
“…The blood-brain barrier disruption and tissue destruction after stroke expose brain epitopes that are normally "invisible" to the immune system. This may induce autoregulatory, anti-inflammatory, and potentially regenerative T-cell responses, 13 or rather prime the immune system to attack the CNS that may be a particular problem in the context of systemic inflammatory response 14 or a second ischemic event. In a mouse model of focal cerebral ischemia we detected increased numbers of myelin oligodendrocyte glycoprotein (MOG) specific T-cells in the spleen, and an increased influx of MOG-specific T-cells into the brain.…”
Section: Does Immunodepression After Stroke Protect the Brain?mentioning
confidence: 99%
“…In the CNS, LPS induces neuroinflammatory responses including microglial activation, astrogliosis, and focal necrosis (Cai et al, 2003;Herber et al, 2006;Pang et al, 2006;Szczepanik et al, 1996). LPS can also augment sensitization to brain antigens (Becker et al, 2005) and induce cross-tolerance (Rosenzweig et al, 2004) in stroke models. LPS is a pathogen-associated molecular pattern (PAMP) and many of its responses are mediated by Toll-like receptor 4 (TLR4) (Lee and Lee, 2002;Palsson-McDermott and O'Neill, 2004).…”
Section: Introductionmentioning
confidence: 99%